The galician atheist. Prophetism, mysticism and romanticism in Aleksander (Leszek) Dunin Borkovsky’s writings - Półchłopek, Tadeusz (Hybris, 2013)
Using the example of Leszek Dunin Borkowski’s works, the author presents a form of a dialogue with a biblical source which was literary prophecy and mysticism. This philosophical basis converted poetic statement into a cultural discourse with traditional forms of religiousness. The outcome of this aesthetics led to the extension of the liberation ideas supporters’ circles as well as to promoting democratic ideas.